2000
DOI: 10.1034/j.1399-3003.2000.16f03.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients hospitalized for COPD have a high prevalence of modifiable risk factors for exacerbation (EFRAM study)

Abstract: There is little information available concerning the extent to which chronic obstructive pulmonary disease (COPD) patients are satisfactorily managed, especially, regards factors supposedly related to COPD exacerbation. The present study assessed the prevalence rates of potentially modifiable risk factors of COPD exacerbation in patients hospitalized for this reason.A systematic sample of one out of two patients admitted for COPD exacerbation, during 1 yr, in four tertiary hospitals in the Barcelona area, Spai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 28 publications
7
83
0
3
Order By: Relevance
“…These deficiencies in outpatient management may be addressed to help limit disease exacerbation. In this same study, previous hospital admissions, lower FEV1 and underprescription of long-term oxygen therapy were independently associated with a higher risk of admission for a COPD exacerbation [79]. Longitudinal studies are urgently needed to assess relevant determinants of COPD-related exacerbations and hospitalisation.…”
Section: Risk For Disease Exacerbationmentioning
confidence: 77%
See 1 more Smart Citation
“…These deficiencies in outpatient management may be addressed to help limit disease exacerbation. In this same study, previous hospital admissions, lower FEV1 and underprescription of long-term oxygen therapy were independently associated with a higher risk of admission for a COPD exacerbation [79]. Longitudinal studies are urgently needed to assess relevant determinants of COPD-related exacerbations and hospitalisation.…”
Section: Risk For Disease Exacerbationmentioning
confidence: 77%
“…KESSLER et al [78] reported that risk factors for hospitalisation included a low body mass index and poor performance on a 6-min walk test, but gas exchange impairment and pulmonary and haemodynamic dysfunction were the most important risks. Importantly, one study suggests that many patients ultimately hospitalised with COPD exacerbation have modifiable characteristics that impact on susceptibility (such as lack of influenza vaccination, improper use of medications, ongoing cigarette smoke exposure) [79]. These deficiencies in outpatient management may be addressed to help limit disease exacerbation.…”
Section: Risk For Disease Exacerbationmentioning
confidence: 99%
“…2 Unfortunately, up to one-third of patients admitted to the hospital for a COPD exacerbation continue to smoke. 3,4 Hospitalization is a potentially effective time to provide evidence-based treatment for tobacco cessation. 5 Patients are already in a tobacco-free environment with access to nurses, physicians and pharmacists able to facilitate treatment.…”
Section: Background and Significancementioning
confidence: 99%
“…Maintenance medications, including inhaled corticosteroids, long-acting b-agonists, and long-acting anticholinergics, have been shown to reduce exacerbations and improve lung function and health-related quality of life among patients with moderate to severe disease (5)(6)(7). Nonetheless, use of and adherence to COPD maintenance medications remain low, ranging from 29 to 56%, and contribute to increased hospitalization, health care costs, and mortality (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%